Discrimination and digital citizenship in postgraduate and specialization environments: A systematic review (2020-2023) - Romani-Miranda, Úrsula Isabel (2023)
This study aims to illuminate the academic landscape pertaining to digital citizenship and discrimination within postgraduate and specialized educational settings, aspiring to decipher the inherent dynamics and suggest trajectories of reflection and action to mitigate the identified disparities. Employing a systematic review methodology through the PRISMA method, a variety of studies from the ERIC and SCOPUS databases were analyzed, revealing a tilt towards the exploration of Digital Citizenship in ERIC, while in SCOPUS, the majority of studies leaned towards Discrimination. Digital Citizenship emerges as a crucial theme, showcasing how technology and the internet modulate civic participation and participatory democracy, whereas Discrimination is primarily examined from a social and educational perspective. The findings exhibit a trend towards evaluating Digital Citizenship as a tool to promote participatory democracy and to understand and address Discrimination in educational settings. It is suggested that these results can be theoretically addressed in studies grounded in the educational reality, nourishing the research lines that are suitable for generating significant changes aimed at the inclusion of vulnerable populations.